Prevalence and factors associated with lipid-lowering medications use for primary and secondary prevention of cardiovascular diseases among Malaysians: the REDISCOVER study - Noorhida Baharudin; Mohamed-Syarif M; Aqil Mohammad Daher; Anis Safura Ramli; Nor-Ashikin Mohamed Noor Khan; Suraya Abdul-Razak (BMC, 2022)
Abstract Background Lipid-lowering medications (LLM) are commonly used for secondary prevention, as well as for primary prevention among patients with high global cardiovascular risk and with diabetes. This study aimed to determine the prevalence of LLM use among high-risk individuals [participants with diabetes, high Framingham general cardiovascular (FRS-CVD) score, existing cardiovascular disease (CVD)] and the factors associated with it. Methods This is a cross-sectional analysis from the baseline recruitment (years 2007 to 2011) of an ongoing prospective study involving 11,288 participants from 40 rural and urban communities in Malaysia. Multiple logistic regression was used to identify characteristics associated with LLM use. Results Majority (74.2%) of participants with CVD were not on LLM. Only 10.5% of participants with high FRS-CVD score, and 17.1% with diabetes were on LLM. Participants who were obese (OR = 1.80, 95% CI: 1.15-2.83), have diabetes (OR = 2.38, 95% CI: 1.78-3.19), have hypertension (OR = 2.87, 95% CI: 2.09-3.95), and attained tertiary education (OR = 2.25, 95% CI: 1.06-4.78) were more likely to be on LLM. Rural residents had lower odds of being on LLM (OR = 0.58, 95% CI: 0.41-0.82). In the primary prevention group, participants with high FRS-CVD score (OR = 3.81, 95% CI: 2.78-5.23) and high-income earners (OR = 1.54, 95% CI: 1.06-2.24) had higher odds of being on LLM. Conclusions LLM use among high CVD-risk individuals in the primary prevention group, and also among individuals with existing CVD was low. While CVD risk factors and global cardiovascular risk score were positively associated with LLM use, sociodemographic disparities were observed among the less-educated, rural residents and low-income earners. Measures are needed to ensure optimal and equitable use of LLM.